The genus Parbatthorax Tanasevitch, 2019 (Araneae, Linyphiidae) new to China, with a new species from the Gaoligong Mountains - Irfan, Muhammad; Peng, Xianjin (European Journal of Taxonomy, 2019)
Parbatthorax proiectus sp. nov. (♂♀) is described from the Gaoligong Mountains in Yunnan, China. A detailed morphological description, photographs of the body and copulatory organs, line drawings of the copulatory organs, as well as a locality map are provided.